Arequipa mining at the beginning of the republic: Between the silver crisis and the gold rush, 1825-1830 - Condori, Víctor (2010)
The changes that occurred in the traditional economy of Arequipa during Independence and the political instability of our first republican years led some local and foreign neighbors and businessmen to direct their hopes, efforts and investments towards an activity little appreciated in colonial Arequipa: mining. . In the midst of this new context, countless companies will emerge, called "companies for mining work"; but there will also be the discovery of one of the most spectacular –and paradoxically less well-known- gold deposits of nineteenth-century Peru. The present work seeks to know the situation of mining in Arequipa during the first republican years and from unpublished material -extracted mainly from local archives- to approach one of the least disclosed gold deposits in regional and national mining history.